Lemna minuta (Araceae, Lemneae), nuevo xenófito para la Flora de Andalucía. - Sánchez Gullón, Enrique; Galán de Mera, Antonio (Acta Botanica Malacitana, 2014)
Lemna minuta, a new xenophyte for the flora of Andalusia Palabras clave. Lemna minuta, xenófito, Huelva, Andalucía, España. Key words. Lemna minuta, xenophyte, Huelva, Andalusia, Spain.